World Association for Sarcoidosis and Other Granulomatous Disease (WASOG) Centers of Excellence - Baughman, Robert P.; Grutters, Jan; Wells, Athol; Azuma, Arata; Costabel, Ulrich; Drent, Marjolein; Lower, Elyse; Culver, Daniel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Editorial